Effects of Solidification Cooling Rate on the Microstructure and Mechanical Properties of a Cast Al-Si-Cu-Mg-Ni Piston Alloy - Tian, Lusha (Materials (Basel), 2018)
The effects of cooling rate 0.15, 1.5, 15, 150, and 1.5 × 105 °C/s on the microstructures and mechanical properties of Al-13Si-4Cu-1Mg-2Ni cast piston alloy were investigated. The results show that with an increase of solidification cooling rate, the secondary dendrite arm spacing (SDAS) of this model alloy can be calculated using the formula D = 47.126v − 1/3. The phases formed during the solidification with lower cooling rates primarily consist of eutectic silicon, M-Mg(2)Si phase, γ-Al(7)Cu(4)Ni phase, δ-Al(3)CuNi phase, ε-Al(3)Ni phase, and Q-Al(5)Cu(2)Mg(8)Si(6) phase. With the increase in the solidification cooling rate from 0.15 to 15 °C/s, the hardness increased from 80.9 to 125.7 HB, the room temperature tensile strength enhanced from 189.3 to 282.5 MPa, and the elongation at break increased from 1.6% to 2.8%. The ε -Al(3)Ni phase disappears in the alloy and the Q phase emerges. The δ phase and the γ phase change from large-sized meshes and clusters to smaller meshes and Chinese script patterns. Further increase in the cooling rate leads to the micro hardness increasing gradually from 131.2 to 195.6 HV and the alloy solidifying into a uniform structure and forming nanocrystals.